Prenatal diagnosis and molecular cytogenetic characterization of partial dup(18q)/del(18p) due to a paternal pericentric inversion 18 in a fetus with multiple anomalies - Min Jin Lee; Sang Hee Park; Sung Han Shim; Myoung-jin Moon; Dong Hyun Cha (Elsevier, 2019)
Objective: We present prenatal diagnosis of rec(18)dup(18q)inv(18)(p11.2q21.2)pat owing to paternal pericentric inversion in a fetus. Case report: A 37-year-old woman was diagnosed with multiple anomalies on a prenatal ultrasound scan at 17 weeks and 5 days of gestation. She underwent amniocentesis at 20 weeks and 2 days. Conventional karyotyping of amniocyte showed 46, XX, der(18). She was thus referred for genetic counseling; cytogenetic analysis revealed a 46, XY karyotype, inv(18)(p11.2q21.2), of the father. Therefore, based on the results of the father, the fetal karyotype was defined as 46, XX, rec(18)dup(18q)inv(18)(p11.2q21.2)pat. Array comparative genomic hybridization of amniocytes to obtain specific information showed a 3-Mb deletion of 18p11.31p11.32 (136227_3100353)x1 and a 23.7-Mb duplication of 18q21.31-q23 (54222717_77957375) × 3. Conclusion: Maternal serum screening produces normal results for 18p-/18q+ syndrome, but it can be diagnosed by fluorescent in situ hybridization, quantitative-fluorescent polymerase chain reaction, or array comparative genomic hybridization test by observing abnormal findings on ultrasound. Keywords: 18p deletion, 18q duplication, Chromosome 18 pericentric inversion, Recombinant chromosome 18